Kontribusi Growth Mindset Terhadap Grit Pada Mahasiswa Yang Sedang Mengerjakan Skripsi - Mawati, Ibtihaj; Primanita, Rida Yanna (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This research aims to see the contribution of growth mindset to grit in students who are working on their thesis. This research applies a correlational quantitative approach. The population of the study were padang state university students who were working on their thesis with a sample size of 175 people determined based on accidental sampling technique. Data collection was carried out using a questionnaire developed by researcher to measure grit and growth mindset based on the grit concept from duckworth (2018) and the growth mindset concept from dweck (2006). Data were analyzed using simple regression. the research results indicated that growth mindset contributed 51.4% to grit.